Plant-Sediment Interactions in Salt Marshes – An Optode Imaging Study of O2, pH, and CO2 Gradients in the Rhizosphere - Koop-Jakobsen, Ketil; Mueller, Peter; Meier, Robert J.; Liebsch, Gregor; Jensen, Kai (Frontiers in Plant Science, 2018)
In many wetland plants, belowground transport of O2 via aerenchyma tissue and subsequent O2 loss across root surfaces generate small oxic root zones at depth in the rhizosphere with important consequences for carbon and nutrient cycling. This study demonstrates how roots of the intertidal salt marsh plant Spartina anglica affect not only O2, but also pH and CO2 dynamics resulting in distinct gradients of O2, pH and CO2 in the rhizosphere. A novel planar optode system (VisiSens TD ®, PreSens GmbH) was used for taking high-resolution 2D-images of the O2, pH and CO2 distribution around roots during alternating light-dark cycles. Belowground sediment oxygenation was detected in the immediate vicinity of the roots resulting in oxic root zones with a 1.7 mm radius from the root surface. CO2 accumulated around the roots, reaching a concentration up to 3-fold higher than the background concentration, and generally affected a larger area within a radius of 12.6 mm from the root surface. This contributed to a lowering of pH by 0.6 units around the roots. The O2, pH and CO2 distribution was recorded on the same individual roots over a diurnal light cycle in order to investigate the interlinkage between sediment oxygenation and CO2 and pH patterns. In the rhizosphere, oxic root zones were affected by illumination of the aboveground biomass, showing higher oxygen concentrations in response to photosynthetic O2 production in light. In darkness, intraspecific differences were observed, where some plants maintained oxic root zones in darkness, while others did not. However, the temporal variation in sediment oxygenation was not reflected in the temporal variations of pH and CO2 around the roots, which were unaffected by changing light conditions at all times. This demonstrates that plant-mediated sediment oxygenation fueling microbial degradation and chemical oxidation have limited impact on the dynamics of pH and CO2 in S. anglica rhizospheres, which may in turn be controlled by other processes such as root respiration and root exudation.